TOTAL AND MATRIC SUCTION MEASUREMENT OF UNSATURATED SOILS IN BAGHDAD REGION BY FILTER PAPER METHOD - Mohammed Y. Fattah; Asma Y. Yahya; Balqees A. Ahmed (Journal of Engineering, 2023)
Soil suction is one of the most important parameters describing the moisture condition of unsaturated soils. The measurement of soil suction is crucial for applying the theories of the engineering behavior of unsaturated soils. The filter paper method is one of the soil suction measurement techniques In this paper, five soil samples were collected from five sites within Baghdad city – al-Rasafa region. These soils have different properties and they were prepared at different degrees of saturation. For each sample, the total and matric suction were measured by the filter paper method at different degrees of saturation. Then correlations were made between the soil properties and the total and matric suction. It was concluded that the suction increases with decrease of the degree of saturation. The relationships between the total and matric suction and the filter paper water content are approximately linear and indicate decrease of suction with increase of the filter paper water content. The total and matric suction increase with the decrease of the soil shear strength.